Topical treatment with gallium maltolate reduces Treponema pallidum subsp. pertenue burden in primary experimental lesions in a rabbit model of yaws. - Lorenzo Giacani; Lawrence R Bernstein; Austin M Haynes; B Charmie Godornes; Giulia Ciccarese; Francesco Drago; Aurora Parodi; Sefora Valdevit; Luca Anselmi; Carlo Francesco Tomasini; Arthur M Baca (Public Library of Science (PLoS), 2019)
Background Gallium is a semi-metallic element known since the 1930s to have antimicrobial activity. This activity stems primarily from gallium's ability to mimic trivalent iron and disrupt specific Fe(III)-dependent pathways, particularly DNA synthesis (due to inhibition of ribonucleotide reductase). Because of its novel mechanism of action, gallium is currently being investigated as a new antibacterial agent, particularly in light of the increasing resistance of many pathogenic bacteria to existing antibiotics. Gallium maltolate (GaM) is being developed as an orally and topically administrable form of gallium. Yaws is a neglected tropical disease affecting mainly the skin and skeletal system of children in underprivileged settings. It is currently the object of a WHO-promoted eradication campaign using mass administration of the macrolide azithromycin, an antibiotic to which the yaws agent Treponema pallidum subsp. pertenue has slowly begun to develop genetic resistance. Methods Because yaws transmission is mainly due to direct skin contact with an infectious skin lesion, we evaluated the treponemicidal activity of GaM applied topically to skin lesions in a rabbit model of yaws. Treatment efficacy was evaluated by measuring lesion diameter, treponemal burden in lesion aspirates as determined by dark field microscopy and amplification of treponemal RNA, serology, and immunohistochemistry of biopsied tissue samples. Results Our results show that topical GaM was effective in reducing treponemal burden in yaws experimental lesions, particularly when applied at the first sign of lesion appearance but, as expected, did not prevent pathogen dissemination. Conclusion Early administration of GaM to yaws lesions could reduce the infectivity of the lesions and thus yaws transmission, potentially contributing to current and future yaws control campaigns.